3D Lattice Engineering of Nanoparticles by DNA Shells. Issue 26 (20th February 2019) - Ji, Min; Ma, Ningning; Tian, Ye
Abstract: With the development of structural DNA nanotechnology, DNA has now far exceeded its original function: as a genetic code. It can, in principle, self‐assemble into desired shapes with accurate size. Moreover, it can perform as a functional linker to program other materials by grafting DNA onto these materials. Nanoparticles, both inorganic and organic, can now be programmatically assembled into complex 3D superlattices with high order when guided by DNA. By encoding functions into the as‐assembled nanoparticles, materials with excellent collective effects may be invented. Here, how nanoparticles with different shapes or functions are successfully fabricated into 3D lattices with the help of DNA shells coated on the surface and how scientists can produce desired lattices by design are reviewed. The cases to achieve dynamic superlattices of nanoparticles by affecting the environment where DNA survives are also discussed. Abstract : 3D lattice engineering of nanoparticles by DNA is reviewed in detail, with a focus on fabrication methods of different lattices and relationships between superlattices and relevant building blocks, including spherical inorganic nanoparticles, anisotropic nanoparticles, and DNA origami frames. Roles of DNA shell are also discussed when achieving dynamic lattices by design.